Entomophagy and entomo-therapeutic practices in a mountainous territory in southeast Guangxi Zhuang Autonomous Region, China - Huimin Luo; Chuanyin Dai; Ping Feng (BMC, 2024)
Abstract Background Although China has a long history of using insects as food and medicine and has developed numerous associated knowledge and practices, especially in its rural and mountainous areas, systematic surveys concerning this subject are limited. In-depth ethnobiological research is needed to compile a comprehensive database of edible and medicinal insects and record the associated knowledge of these food and medicinal resources. Methods Data on edible and medicinal insects and associated knowledge about them were collected by interviewing 216 local villagers in a mountainous territory in southeast Guangxi Zhuang Autonomous Region, China. Results Local villagers used at least 16 edible and 9 medicinal insects, of which 4 wasp species were used in both entomophagy and medicinal practices. Parapolybia varia, Polistes olivaceus, and Anomala chamaeleon were newly recorded edible insects in China. The wasps, Euconocephalus sp., Gryllotalpa orientalis, and Cyrtotrachelus longimanus, were preferred and culturally important edible insects. Populations of Euconocephalus sp. and G. orientalis were reported to have substantially decreased in recent years. Wasps and a bamboo bee were used to treat rheumatism, while cockroaches and antlions were used to treat common cold symptoms in infants. Insect-related knowledge was positively correlated with the interviewees' age. Conclusions Villagers have accumulated considerable local and traditional knowledge of entomophagy and entomo-therapeutic practices. However, this knowledge is in danger of being lost, which highlights the urgent need to document this information. Edible insects enrich local diets, and a more sustainable supply (such as through insect farming) could maintain local entomophagy practices. Medicinal insects are a part of local folk medicine, and pharmacological and chemical techniques could be applied to identify various biologically active substances in these insects.